2002
DOI: 10.1006/dbio.2002.0668
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog Signaling from the Urethral Epithelium Controls External Genital Development

Abstract: External genital development begins with formation of paired genital swellings, which develop into the genital tubercle. Proximodistal outgrowth and axial patterning of the genital tubercle are coordinated to give rise to the penis or clitoris. The genital tubercle consists of lateral plate mesoderm, surface ectoderm, and endodermal urethral epithelium derived from the urogenital sinus. We have investigated the molecular control of external genital development in the mouse embryo. Previous work has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
392
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(411 citation statements)
references
References 82 publications
15
392
2
1
Order By: Relevance
“…Our results also show that proliferation and Ig secretion by GC B cells are reduced when Hh signaling is inhibited, but these effects are probably the consequence of the decreased GC B cell survival observed. Antiapoptotic effects of Shh have been also demonstrated during development of the nervous system (45), teeth (59), and external genitalia (46), as well as in somite cells (48), keratinocytes (49), thymocytes (60), T lymphocytes (29), and certain neuron populations (47). In GCs, three types of stimuli seem to prevent apoptosis in GC B cells: ligation of the BCR, ligation of CD40, and unknown signals delivered by FDCs (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also show that proliferation and Ig secretion by GC B cells are reduced when Hh signaling is inhibited, but these effects are probably the consequence of the decreased GC B cell survival observed. Antiapoptotic effects of Shh have been also demonstrated during development of the nervous system (45), teeth (59), and external genitalia (46), as well as in somite cells (48), keratinocytes (49), thymocytes (60), T lymphocytes (29), and certain neuron populations (47). In GCs, three types of stimuli seem to prevent apoptosis in GC B cells: ligation of the BCR, ligation of CD40, and unknown signals delivered by FDCs (33).…”
Section: Discussionmentioning
confidence: 99%
“…Given that Shh has been described as an antiapoptotic factor for several cell types (29,(45)(46)(47)(48)(49), we decided to examine whether Shh also affected the survival of GC B cells. Isolated GC cells were cultured in the presence or the absence of Hh signaling inhibitors, and the proportion of annexin V-positive dying cells was assessed in the B220 ϩ PNA high GC B cell population.…”
Section: Hh Signaling Blockade Affects Gc B Cell Viabilitymentioning
confidence: 99%
“…The phenotypes of gene knockout mice have revealed that several growth and signaling factor families play fundamental roles in reproductive and urogenital organ formation (Batourina et al, 2002;Doles et al, 2006;Haraguchi et al, 2001;Haraguchi et al, 2000;Huang et al, 2005;Jamin et al, 2002;Kobayashi and Behringer, 2003;Kondo et al, 1996;McMahon et al, 2003;Morgan et al, 2003;Perriton et al, 2002;Suzuki et al, 2003). Shh is expressed in the cloacal epithelia and is vital for the regulation of structures derived from the genital tubercle (GT) and the urogenital sinus, such as the external genitalia and the prostate, respectively (de Santa Barbara and Roberts, 2002;Freestone et al, 2003;Pu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shh is expressed in the cloacal epithelia and is vital for the regulation of structures derived from the genital tubercle (GT) and the urogenital sinus, such as the external genitalia and the prostate, respectively (de Santa Barbara and Roberts, 2002;Freestone et al, 2003;Pu et al, 2004). Shh null mouse embryos display GT agenesis associated with aberrant cloacal formation, suggesting that Shh signals emanating from the epithelium of the cloaca may play an essential role in peri-cloacal mesenchyme (PCM) development (Haraguchi et al, 2001;Perriton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic endoderm gives rise to the bladder urothelium while the connective tissues and smooth muscle of the developing bladder are derived from the peri-cloacal mesenchyme (Haraguchi et al, 2007;Brenner-Anantharam et al, 2007). Genetic studies indicate the homeobox genes play an important role in determining the global patterning of the urogenital system (Satokata et al, 1995;Sciavolino et al, 1997;Warot et al, 1997;Goodman and Scambler, 2001;de Santa and Roberts, 2002;Troy et al, 2003), while key signaling molecules like sonic hedgehog and wnts have been implicated in determining the regional patterning within specific urogenital organs (Perriton et al, 2002;Freestone et al, 2003;Mericskay et al, 2004). The differentiation program responsible for the development of smooth muscle involves the complex interaction of epigenetic and genetic events including chromatin remodeling and acetylation, the SRF-myocar-din pathway, basic helix-loop-helix factors, AP-1 complex genes, and the ternary complex factors of the ETS domain family (Manabe and Owens, 2001;Chen et al, 2002;Du et al, 2003;Kumar and Owens, 2003;Miano, 2003;Wang et al, 2003Wang et al, , 2004Yoshida et al, 2003;Buchwalter et al, 2004;Spin et al, 2004;McDonald et al, 2006;Pipes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%